PHASE TRANSFORMATION IN THE FORMATION OF FAUJASITE FROM FLY ASH - Sutarno Sutarno; Yateman Arryanto (Indonesian Journal of Chemistry, 2005)
Faujasite was hydrothermally synthesized from fly ash at 100oC in alkaline solution by reflux with 5M HCl and fusion with NaOH pretreatments. Phase transformation in the formation of faujasite was performed by variation of NaOH/fly ash weight ratios and hydrothermal times. The solid products were characterized by X-ray diffraction method. Results showed that faujasite was formed through dissolution of fly ash components such as quartz, mullite and amorphous aluminosilicates followed by crystallization to form faujasite. Arranging the NaOH/fly ash weight ratio as well as hydrothermal time can selectively form faujasite. Faujasite with crystallinity of 97.06%, Si/Al ratio of 2.68, and specific surface area of 452.93 m2/g was successfully formed using NaOH/fly ash weight ratio of 1.2 for hydrothermal time of 72 hours. In more concentrated alkaline solution as well as for longer hydrothermal time, faujasite was completely transformed into hydroxysodalite as the final product.